Simulating the Potential Impacts of COVID-19 School Closures on Schooling and Learning Outcomes : A Set of Global Estimates - Azevedo, Joao Pedro (World Bank, Washington, DC, 2020)
School closures due to COVID-19 have left more than a billion students out of school. This paper presents the results of simulations considering three, five and seven months of school closure and different levels of mitigation effectiveness resulting in optimistic, intermediate and pessimistic global scenarios. Using data on 157 countries, the analysis finds that the global level of schooling and learning will fall. COVID-19 could result in a loss of between 0.3 and 0.9 years of schooling adjusted for quality, bringing down the effective years of basic schooling that students achieve during their lifetime from 7.9 years to between 7.0 and 7.6 years. Close to 7 million students from primary up to secondary education could drop out due to the income shock of the pandemic alone. Students from the current cohort could, on average, face a reduction of $355, $872, or $1,408 in yearly earnings. In present value terms, this amounts to between $6,472 and $25,680 dollars in lost earnings over a typical student's lifetime. Exclusion and inequality will likely be exacerbated if already marginalized and vulnerable groups, like girls, ethnic minorities, and persons with disabilities, are more adversely affected by the school closures. Globally, a school shutdown of 5 months could generate learning losses that have a present value of $10 trillion. By this measure, the world could stand to lose as much as 16 percent of the investments that governments make in the basic education of this cohort of students. The world could thus face a substantial setback in achieving the goal of halving the percentage of learning poor and be unable to meet the goal by 2030 unless drastic remedial action is taken.